2017
DOI: 10.1111/1541-4329.12103
|View full text |Cite
|
Sign up to set email alerts
|

Use of Exam Wrappers to Enhance Students’ Metacognitive Skills in a Large Introductory Food Science and Human Nutrition Course

Abstract: Research shows that students struggle to develop higher order thinking skills and effective study strategies during the transition from high school to college. Therefore, in addition to teaching course content, effective instructors should assist students in developing metacognitive skills, that is, the practice of thinking about their thinking. An effective assignment that assists students in thinking about their exam performance is the exam wrapper. The objectives of this study were to examine students' meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 10 publications
2
55
1
Order By: Relevance
“…We observed this pattern in both semesters, as higher-performing students had significantly higher calibration scores, and thus higher postdiction accuracy, than their lower-performing counterparts. We also found that students who over-estimated their exam performance in both semesters had significantly lower exam scores than students who under-estimated, which is consistent with the findings of previous studies ( 6 , 8 , 22 ). Aligned with the goals of the curriculum, we observed a significant decrease in over-postdictors from Exam 1 to Exam 3 in both semesters, and also found that lower-performing students exhibited a significant increase in postdiction accuracy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed this pattern in both semesters, as higher-performing students had significantly higher calibration scores, and thus higher postdiction accuracy, than their lower-performing counterparts. We also found that students who over-estimated their exam performance in both semesters had significantly lower exam scores than students who under-estimated, which is consistent with the findings of previous studies ( 6 , 8 , 22 ). Aligned with the goals of the curriculum, we observed a significant decrease in over-postdictors from Exam 1 to Exam 3 in both semesters, and also found that lower-performing students exhibited a significant increase in postdiction accuracy.…”
Section: Discussionsupporting
confidence: 91%
“…Why or Why not?”), and 3) to further describe the study strategies and behaviors that worked for them or that needed to change for improved performance on the next exam ( Appendix 2 ). This assignment is similar to cognitive wrappers or exam wrappers that have been employed across disciplines to help students improve their learning and self-regulatory skills ( 21 , 22 ). See Andaya ( 15 ) for a full description of the Exam Review activity used in this study and its impact on students.…”
Section: Methodsmentioning
confidence: 99%
“…Exam wrappers: Exam wrappers are short, reflective writing activities that asked students to review their applied study strategies in relation to their performance on an exam with a focus on adjusting their future learning practices. Reference: Gezer-Templeton, Mayhew, Korte, and Schmidt (2017).…”
Section: Course Assignmentsmentioning
confidence: 99%
“…In addition to having positive impact, or at least no negative one, exam-wrappers are easy to implement. According to Gezer-Templeton et al, wrappers require short time for both, students to fill and instructors to prepare and assess, mostly because it is two pages at most, of short-answer questions [15]. Further, they are repeatable and can be adapted from course to course easily.…”
Section: Literature Reviewmentioning
confidence: 99%